Radiation protection in radiological imaging: a survey of imaging modalities used in Japanese institutions for verifying applicator placements in high-dose-rate brachytherapy. (6th October 2020) - Okamoto, Hiroyuki; Kito, Satoshi; Tohyama, Naoki; Yonai, Shunsuke; Kawamorita, Ryu; Nakamura, Masaru; Fujimoto, Takahiro; Tani, Syoji; Yomoda, Akihiro; Isobe, Toru; Furukawa, Hiroshi; Kotaka, Kikuo; et al.
Abstract: Institutional imaging protocols for the verification of brachytherapy applicator placements were investigated in a survey study of domestic radiotherapy institutions. The survey form designed by a free on-line survey system was distributed via the mailing-list system of the Japanese Society for Radiation Oncology. Survey data of 75 institutions between August 2019 and October 2019 were collected. The imaging modalities used were dependent on resources available to the institutions. The displacement of a brachytherapy applicator results in significant dosimetric impact. It is essential to verify applicator placements using imaging modalities before treatment. Various imaging modalities used in institutions included a computed tomography (CT) scanner, an angiography X-ray system, a multi-purpose X-ray system and a radiotherapy simulator. The median total exposure time in overall treatment sessions was $\le$ 75 s for gynecological and prostate cancers. Some institutions used fluoroscopy to monitor the brachytherapy source movement. Institutional countermeasures for reducing unwanted imaging dose included minimizing the image area, changing the imaging orientation, reducing the imaging frequency and optimizing the imaging conditions. It is worth noting that half of the institutions did not confirm imaging dose regularly. This study reported on the usage of imaging modalities for brachytherapy in Japan. More caution should be applied with interstitial brachytherapy with many catheters that can lead to potentially substantial increments in imaging doses for monitoring the actual brachytherapy source using fluoroscopy. It is necessary to share imaging techniques, standardize imaging protocols and quality assurance/quality control among institutions, and imaging dose guidelines for optimization of imaging doses delivered in radiotherapy should be developed.